Activation of graphitic nitrogen sites for boosting oxygen reduction. (15th April 2020) - Chao, Guojie; Zhang, Longsheng; Wang, Dong; Chen, Shan; Guo, Hele; Xu, Kaibing; Fan, Wei; Liu, Tianxi
Abstract: Carbon materials doped with sulfur (S) and nitrogen (N) are prospective alternatives to Pt-based catalysts as oxygen reduction reaction (ORR) catalyst since they are inexpensive and highly catalytic active. However, the further advancement of catalysts is greatly hindered for its unclear and equivocal catalytic sites. Here, using density functional theory studies, we find that those inactive carbon atoms next to graphitic N become ORR catalytic sites after S doping, which is distinctly different from N-doped carbon materials where catalytic sites are introduced by pyridinic N. The electrochemical results show that increasing the content of graphitic N can lead to higher catalytic activity for S and N dual-doped carbon materials, which exhibits higher turnover frequency towards ORR than that of N-doped carbon materials. This work provides insights for further advancement of electrocatalysts via heteroatom doping. Graphical abstract: Image 1